Semantic Support for Scenarios to Improve Communication in Agribusiness - Antonelli, Leandro (2019)
Organizations produce and exchange a lot of critical information to obtain good results. Systems developed in different domains are adapted to be integrated when they need to exchange information. Food and agribusiness are not the exceptions, they are pioneers in the use of massive data and collaboration. One of the biggest challenges to communicate software systems is analyzing their colliding context. Every software system relies on its own context, with its rules, dynamic, and language. It is a big effort to have a complete understanding of the composed domain. Scenarios are well-known tools to describe domains and are commonly described with text. When Scenarios are built by different stakeholders it is extremely important to review them in order to unify their description. Thus, the improved Scenarios with a unified point of view make it possible an analysis to identify the relationship between two different domains. This analysis is the key to design a mechanism to exchange information. This paper proposes a semantic definition of Scenarios and a set of queries to identify issues in the Scenarios and improve their quality. We also provide a wiki platform to implement the semantic support and the queries.